MM31/EIR1 promotes lateral root formation in Arabidopsis - Honda, Hiroaki (Landes Bioscience, 2011)
Lateral root formation in Arabidopsis provides a model for the study of auxin function. Tryptophan (Trp) is a precursor of the auxin indoleacetic acid (IAA). To study the physiological function of Trp in auxin-related phenotypes, we examined the effect of Trp on lateral root formation. We found that Trp treatment enhanced lateral root formation and, by screening for mutants in which the effect of Trp on lateral root formation was enhanced, we isolated the mm31 mutant. Based on genetic and physiological analyses, we propose that MM31/EIR1 modulates lateral root formation by regulating the IAA polar transport system, and that auxin transport from the shoot to the root regulates lateral root formation.